2016
DOI: 10.1177/0194599815627624
|View full text |Cite
|
Sign up to set email alerts
|

Features of Residual Dizziness after Canalith Repositioning Procedures for Benign Paroxysmal Positional Vertigo

Abstract: RD is a common self-limited disorder, more frequent in the elderly, which may occur after the physical treatment for BPPV. The DHI score at the time of BPPV diagnosis represents a useful tool to quantify the impact of this vestibular disorder on the quality of life and to estimate the risk of RD after CRPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 34 publications
3
65
1
4
Order By: Relevance
“…31 A recent study confirmed a significant association with older age and anxiety, in particular with higher DHI questionnaire score in emotional domain, which appears to be the most important predictor factor for the occurrence of RD. 32 Concurrent chronic diseases including hypertension, diabetes mellitus, heart disease, and hyperlipidemia were not significantly correlated with RD. 17 …”
Section: Resultsmentioning
confidence: 90%
“…31 A recent study confirmed a significant association with older age and anxiety, in particular with higher DHI questionnaire score in emotional domain, which appears to be the most important predictor factor for the occurrence of RD. 32 Concurrent chronic diseases including hypertension, diabetes mellitus, heart disease, and hyperlipidemia were not significantly correlated with RD. 17 …”
Section: Resultsmentioning
confidence: 90%
“…The support utilization refers to the pattern of behavior that an individual utilizes when seeking social support. It is well known that anxiety and dizziness are comorbid symptom, and anxiety has been demonstrated to play a contributory role in dizziness [1][2][3]26]. In this study, for patients with RD, the ability to deal with daily work and interact with others was impaired because of the functional limitation in daily living, and the feelings of insecurity, anxiety, and depression experienced by patients as result of their disorders.…”
Section: Duan/fu/tang/liu/liu/chen/zhangmentioning
confidence: 79%
“…Benign Paroxysmal Positional Vertigo (BPPV), characterized by short repeated episodes of mild to intense vertigo triggered by changes in head position, and accompanied by imbalance and nausea, is the most common cause for peripheral vestibular vertigo [1,2]. The suggested pathophysiology is that otoconia derived from the utricular macula moves to the semicircular canal [3][4][5]. The movement of the otoconial matter due to gravity causes the flow of endolymph, which consequently induce vertigo and nystagmu.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aunque en la actualidad se acepta que el tratamiento gold standard del VPPB son las maniobras de reposición canalicular, algunos pacientes manifiestan en las semanas posteriores a su recuperación con este tratamiento, síntomas de mareo e inestabilidad persistente sin nistagmo ni sensación vertiginosa en posiciones estáticas o dinámicas posiblemente en relación con la alteración de la información propioceptiva y visual [28,29]. La aparición de este cuadro se ha relacionado con factores tales como la edad, el tiempo de evolución del cuadro de VPPB [30,31] o con un componente de ansiedad.…”
Section: Inestabilidad Residual Tras El Vértigo Posicional Paroxísticunclassified